Blood flow restriction during self-paced aerobic intervals reduces mechanical and cardiovascular demands without modifying neuromuscular fatigue - Smith, N. D.; Girard, O.; Scott, B. R.; Peiffer, J. J. (European Journal of Sport Science, 2023)
This study examined cardiovascular, perceptual and neuromuscular fatigue characteristics during and after cycling intervals with and without blood flow restriction (BFR). Fourteen endurance cyclists/triathletes completed four 4-minute self-paced aerobic cycling intervals at the highest sustainable intensity, with and without intermittent BFR (60% of arterial occlusion pressure). Rest interval durations were six, four and four minutes, respectively. Power output, cardiovascular demands and ratings of perceived exertion (RPE) were averaged over each interval. Knee extension torque and vastus lateralis electromyography responses following electrical stimulation of the femoral nerve were recorded pre-exercise, post-interval one (+1, 2 and 4-minutes) and post-interval four (+1, 2, 4, 6 and 8-minutes). Power output during BFR intervals was lower than non-BFR (233 ± 54 vs 282 ± 60 W, p < 0.001). Oxygen uptake and heart rate during BFR intervals were lower compared to non-BFR (38.7 ± 4.5 vs 44.7 ± 6.44 mL kg-1 min-1, p < 0.001; 160 ± 14 vs 166 ± 10 bpm, p < 0.001), while RPE was not different between conditions. Compared to pre-exercise, maximal voluntary contraction torque and peak twitch torque were reduced after the first interval with further reductions following the fourth interval (p < 0.001) independent of condition (p = 0.992). Voluntary activation (twitch interpolation) did not change between timepoints (p = 0.375). Overall, intermittent BFR reduced the mechanical and cardiovascular demands of self-paced intervals without modifying RPE or knee-extensor neuromuscular characteristics. Therefore, BFR reduced the cardiovascular demands while maintaining the muscular demands associated with self-paced intervals. Self-paced BFR intervals could be used to prevent cardiovascular and perceptual demands being the limiting factor of exercise intensity, thus allowing greater physiological muscular demands compared to intervals without BFR.